Implementasi Model Pembelajaran Student Facilitator and Explaining (SFE) dalam Meningkatkan Keterampilan Berbicara pada Pembelajaran Bahasa Indonesia - Anelta, Shella; Popo Hardi, Sean; El Widdah , Minnah (FAKULTAS AGAMA ISLAM UNIVERSITAS BILLFATH, 2024)
This research describes the implementation of the student facilitator and explaining learning model for class V students in Indonesian language learning at SDN 114/VII Bukit Kalimau Ulu I. The objectives of this research are to determine the implementation of the student facilitator and explaining learning model for students. In this research, researchers used qualitative methods. The data collection techniques include observation, interviews and documentation. From the research obtained by the researcher as well as an examination of existing theories, the author concluded that: 1) The implementation was carried out in three stages. First, the teacher's preliminary activities carried out classroom conditioning, conveying learning objectives, conveying material through concept maps. Second, the teacher's core activity is implementing the steps of the Student Facilitator and Explaining learning model to students. Third, the closing activity is that the teacher carries out elaboration. 2) supporting factors and inhibiting factors in this learning model, namely supporting factors, namely rewards for students so that student motivation grows. Meanwhile, inhibiting factors are students' lack of desire to develop, students not being sure about their opinions and students' lack of knowledge. 3) Teachers create active learning. Students are given the opportunity to explain or explain the material to their friends. Students who previously lacked confidence, but by seeing their friends explain the material, little by little they tried and finally they were able to explain with their own opinions.